2014
DOI: 10.1111/joss.12087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Familiarity on a Cross‐Cultural Acceptance of a Sweet Ethnic Food: A Case Study withKorean Traditional Cookie (Yackwa)

Abstract: This study was conducted to understand the relationship between familiarity and cross-cultural acceptance for an ethnic sweet treat (Yackwa; Korean traditional cookie) by Korean, Japanese and French consumers. Descriptive analysis and consumer testing were performed on six Yackwa samples. Overall, the samples received favorable responses from the foreign consumers. Korean consumers liked samples with a soft and cohesive texture, whereas Japanese and French consumers liked flaky and crispy texture. French consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 32 publications
4
57
0
Order By: Relevance
“…In addition, Figure (C) shows that they liked the Seolgitteok sample with the highest amount of sugar (W25B75_H) significantly more than those with lower amounts of sugar (W75B25_L and B100_L), indicating that U.S. consumers prefer highly sweetened Seolgitteok ; the traditional Seolgitteok is made with half the amount (10%) of that of the sample with the highest level (20%) of sugar. This result is consistent with the previous findings that Europeans and North Americans preferred sweetness more than did Asians (Bertino and others ; Hong and others ). In addition, Asian people have previously been found to be more sensitive and discriminating with respect to sweet‐tasting stimuli than North American people (Bertino and others ; Ishii and others ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, Figure (C) shows that they liked the Seolgitteok sample with the highest amount of sugar (W25B75_H) significantly more than those with lower amounts of sugar (W75B25_L and B100_L), indicating that U.S. consumers prefer highly sweetened Seolgitteok ; the traditional Seolgitteok is made with half the amount (10%) of that of the sample with the highest level (20%) of sugar. This result is consistent with the previous findings that Europeans and North Americans preferred sweetness more than did Asians (Bertino and others ; Hong and others ). In addition, Asian people have previously been found to be more sensitive and discriminating with respect to sweet‐tasting stimuli than North American people (Bertino and others ; Ishii and others ).…”
Section: Resultssupporting
confidence: 93%
“…The x‐axis (t1) and the y‐axis (t2) represent the added levels of sugar and white rice flour, respectively. The W25B75_H sample, the one most favored by U.S. consumers (Figure ), was found to be associated with “sweet taste,” “metallic flavor,” “adhesiveness to teeth,” “moistness of mass,” and “roughness of mass.” This result supports the previous research that North Americans preferred sweetness more than did Asians (Bertino and others ; Hong and others ). Although healthiness was considered as the reason for liking of Korean style beverages among Korean consumers, sweetness was found to be one of positive attributes of preferred Korean style beverages among the U.S. consumers (Chung and others ).…”
Section: Resultssupporting
confidence: 92%
“…This may be due to greater familiarity with milk and whey proteins and their specific health benefits. Studies have proved the positive effect of familiarity (with a product or concept) on liking (Hansen and Wänke ; Hong and others ). Milk and whey proteins have been shown to have health benefits beyond basic nutrition such as bioactive compounds with antimicrobial or antiviral activity, immune promoting compounds, anticarcinogenic properties and cardiovascular health‐promoting features (Solak and Akin ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of familiarity and perceptual fluency on cross-cultural acceptance of an ethnic food was reported by Hong et al [4], who presented a case study on a Korean traditional cookie, Yackwa. This study involved Korean, Japanese, and French consumers and showed that Korean consumers liked samples with a soft and cohesive texture, whereas Japanese and French consumers liked a flaky and crispy texture.…”
Section: Introductionmentioning
confidence: 89%